2023
DOI: 10.3389/fimmu.2023.1135657
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer immune infiltration microenvironment identification, construction of immune scores, assisting patient prognosis and immunotherapy

Abstract: BackgroundThe immune microenvironment is of great significance in cervical cancer. However, there is still a lack of systematic research on the immune infiltration environment of cervical cancer.MethodsWe obtained cervical cancer transcriptome data and clinical information from the Cancer Genome Atlas (TCGA) and the Gene Expression Omnibus (GEO) databases, evaluated the immune microenvironment of cervical cancer, determined immune subsets, constructed an immune cell infiltration scoring system, screened key im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 73 publications
2
5
0
Order By: Relevance
“…26 Therefore, the tumor immune microenvironment plays a pivotal significance in CC. 27 In our study, KIF23 and CEP55 were found to be positively correlated with tumor purity. Similarly, EZH2 had a positive correlation with CD4 + T cells and MELK with neutrophils and dendritic cells.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…26 Therefore, the tumor immune microenvironment plays a pivotal significance in CC. 27 In our study, KIF23 and CEP55 were found to be positively correlated with tumor purity. Similarly, EZH2 had a positive correlation with CD4 + T cells and MELK with neutrophils and dendritic cells.…”
Section: Discussionsupporting
confidence: 57%
“…In a variety of malignancies, the histone methyl transferase EZH2 has pro‐oncogenic and immunomodulatory effects 26 . Therefore, the tumor immune microenvironment plays a pivotal significance in CC 27 . In our study, KIF23 and CEP55 were found to be positively correlated with tumor purity.…”
Section: Discussionsupporting
confidence: 54%
“…PD-1/PD-L1 overexpression (T cells, DCs, and macrophages) is well correlated with high-risk HPV infection and its progression to the CC with increased mortality by supporting the immunosuppressive TIME (Figure 3) [110,[112][113][114][115][116][117]. Cytotoxic T-lymphocyteassociated protein 4 (CTLA-4, another immune checkpoint) overexpression is also associated with CC immunosuppressive TIME (Figure 3) by increasing regulatory T cells' (T regs ) and conventional T cells' antitumor function by regulating CD28 signaling that impacts their interaction with CD80 (B7.1) and CD86 (B7.2) [118,119]. Increased CTLA4 levels also correlate with IL-1β expression CC as IL-1β increases the signal transduction of the CTLA4; therefore, targeting the IL-1β-CTLA4 axis may help to overcome the CC immunosuppressive TIME, as seen in colon cancer [118,120].…”
Section: Factors Regulating CC Immunosuppressive Timementioning
confidence: 99%
“…Cytotoxic T-lymphocyteassociated protein 4 (CTLA-4, another immune checkpoint) overexpression is also associated with CC immunosuppressive TIME (Figure 3) by increasing regulatory T cells' (T regs ) and conventional T cells' antitumor function by regulating CD28 signaling that impacts their interaction with CD80 (B7.1) and CD86 (B7.2) [118,119]. Increased CTLA4 levels also correlate with IL-1β expression CC as IL-1β increases the signal transduction of the CTLA4; therefore, targeting the IL-1β-CTLA4 axis may help to overcome the CC immunosuppressive TIME, as seen in colon cancer [118,120]. Cystatin 7 (CST7) in T cells is also downregulated in the CC patients which induces dysfunctional antitumor CD4 + and CD8 + T cell immunity [118,121].…”
Section: Factors Regulating CC Immunosuppressive Timementioning
confidence: 99%
See 1 more Smart Citation